2011
DOI: 10.1002/lt.22348
|View full text |Cite
|
Sign up to set email alerts
|

Should the liver transplant criteria for hepatocellular carcinoma be different for deceased donation and living donation?

Abstract: Should the liver transplant criteria for hepatocellular carcinoma (HCC) be different for deceased donation and living donation? Living donor liver transplantation (LDLT) for HCC offers the opportunity to provide a neoadjuvant treatment organized around a scheduled time for the transplant and to restore excellent liver function with a high-quality graft. However, some centers have been reluctant to offer LDLT for HCC because of concerns about higher rates of cancer recurrence and inferior patient survival after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
(39 reference statements)
0
15
0
Order By: Relevance
“…A recent review article by experts [29] concluded as follows: Although there is no strong evidence to support the higher HCC recurrence rates in LDLT than DDLT, the higher recurrence rates in LDLT recipients reported by several authors cannot be ignored. Actually, there are critical differences among societies such as: (1) differences in the allocation system for DDLT and LDLT; (2) differences in the availability of deceased donors; (3) differences in the potential waiting time; and (4) the differences in regional and national organ transplant law.…”
Section: Current Opinions Regarding the Difference Between Ldlt And Ddltmentioning
confidence: 99%
“…A recent review article by experts [29] concluded as follows: Although there is no strong evidence to support the higher HCC recurrence rates in LDLT than DDLT, the higher recurrence rates in LDLT recipients reported by several authors cannot be ignored. Actually, there are critical differences among societies such as: (1) differences in the allocation system for DDLT and LDLT; (2) differences in the availability of deceased donors; (3) differences in the potential waiting time; and (4) the differences in regional and national organ transplant law.…”
Section: Current Opinions Regarding the Difference Between Ldlt And Ddltmentioning
confidence: 99%
“…A review article by experts (27) concluded as follows: although there is no strong evidence to support the higher HCC recurrence rates in LDLT than DDLT, the reported higher recurrence rates in LDLT recipients cannot be ignored. In addition to taking into account the differences in organ allocation, graft availability, and organ transplant law and allocation system, liver transplant candidates with HCC and their potential live donors should be informed following risks and benefits; the waiting time for DDLT may lead to the dropout due to HCC progression which could be avoided by the prompt LDLT, however, the prompt LDLT may mask the aggressive tumor characteristics which may lead to a higher HCC recurrence rates.…”
Section: Systematic Review and Meta-analysismentioning
confidence: 99%
“…This suggests that perhaps the wait for the organ in the DDLT situation may select patients with better tumor biology for transplant. 7 It may also be that patients beyond Milan criteria progress while waiting for a deceased donor liver while they may have considerably superior outcomes in the LDLT scenario where this wait is eliminated.…”
Section: The Milan Criteriamentioning
confidence: 99%